Evaluation of categories of intrapartum fetal heart rate tracings in pregnancies complicated with fetal growth restriction and its relation to perinatal outcome - H. U., Bhavya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Intrapartum FHR monitoring is widely used during labour as changes in FHR precede brain injury, so timely response to abnormal FHR patterns might be effective in preventing it. There is a strong association between stillbirth and FGR which warrants intensive intrapartum fetal surveillance for optimal perinatal outcome. In this study we aimed to classify intrapartum FHR tracings into different categories in FGR pregnancies and correlate with perinatal outcome. Methods: A total 100 singleton pregnant women >34 weeks gestation with FGR were included in study. FHR tracings were followed throughout first and second stage of labour. FHR tracing were categorized into NICHD 3-tier classification as category I, II and III. Maternal and neonatal outome in each category were analysed. Results: Mean duration of category I tracings was 9.05 hours, category II was 7.66 hours and that of category III was 0.49 hours. During late active phase 25/95 patients with category I FHR tracings had vaginal delivery, 62/95 had category II FHR tracings, of which 95.1% had vaginal delivery and 4.9% had instrumental. 8/95 with category III FHR tracings required caesarean section. All patients with category I tracings had normal neonatal outcome, among patients with category II FHR tracings, 74.6% had normal whereas 25.4% had adverse outcome, all with category III FHR tracings had adverse outcome. Conclusions: Categorizing FHR tracings is helpful to distinguish neonates who are likely to have normal outcome from those who are at risk for fetal hypoxia. When the category II tracings are present, it requires more vigilant monitoring and decision taking.